Pengaruh Citra Merek, Konten Pemasaran, dan Persepsi Kualitas Terhadap Niat Beli Produk Serum Somethinc di Provinsi DKI Jakarta - Fania Arfiana; Yennida Parmariza (Universitas Mercu Buana, 2025)
This study aims to analyze the influence of brand image, content marketing, and perceived quality on the purchase intention towards Somethinc’s serum product in DKI Jakarta. Population in this research is the DKI Jakarta citizens. The sample used is 120 DKI Jakarta citizens with the age 18-30 years old. The sampling method uses Purposive Sampling. The methods of data collecting using survey method, with the research instrument is a questionnaire. The data analysis method using Partial Least Square with SmartPLS 4.0 version software. With the questionnaire research instrument, the result of this study are Brand Image has no significant effect on Purchase Intention, Content marketing has a positive and significant effect on Purchase Intention, and Perceived Quality has a positive and significant effect on Purchase Intention.